KAPASITAS PEMERINTAH DAERAH DALAM PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH DI MASA PANDEMI COVID-19 - Irma Purnamasari; Denny Hernawan; Sri Hastuti (Jurnal Governansi, 2022)
Micro, Small and Medium Enterprises (MSMEs) are business activities that are able to expand employment opportunities and can play a role to improve equity and income of people. Therefore, the development of MSMEs still faces various constraints that need attention from various parties, especially the government, both central and local one. This research aims to find out the capacity of local government in empowering MSMEs during COVID-19 pandemic in Sukabumi City. The capacity of local government is based on three levels, namely system level, organizational/institutional level, and individual/human resource level. Method of this research is descriptive-qualitative method by maximizing primary and secondary data. Collection of primary data uses interview and observation, meanwhile secondary data are collected by documentation. The collected data are qualitatively described. Results of this research indicate that the capacity of local government based on system level, organizational/institutional level, and individual/human resource level is needed in empowering MSMEs during COVID-19 pandemic in Sukabumi City. The capacity building of local government of Sukabumi City has been conducted but it is not optimal yet and therefore the capacity building of local government is needed to improve the contribution of MSMEs on the local economy. Key words: COVID-19 Pandemic, Empowerment, Local Government Capacity, Micro, Small and Medium Enterprises.